Thursday
March 30, 2017

Post a New Question

Posted by on .

I have to find the inverse function of f(x)=3-4x. I got y=3-x/4 for the function. I then have to plug it back into the function and verify that it is the inverse. So I wrote (3-4(3-x))/4. This resulted in (-3+x)/4=x. I tried isolating it to get x=x but I just can't get it. Where did I goof up?

  • Algebra - ,

    if g(x) is the inverse of f(x), then
    f(g(x)) should equal x.
    You proved that....
    f(inverse)=(3-4(3-x))/4=x

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question